Klarifikasi al-DarwÃ®sh atas Pandangan Orientalis tentang Kontradiksi Ayat al-Qurâan dengan Kaidah Nahw - Tidjani, Amnah (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
This paper will examine clarification Muhy al-DÃ®n al-DarwÃ®sh against charges orientalistabout the authenticity of the Koran. Today, these allegations go back voiced by the Egyptian Coptic priest Zakaria Batrousin his book TasÃ¢ulÃ¢t Hawl al-QurâÃ¢n. One of the accused is the assertion that the Koran contains errors and defects in terms of language, as it is considered contrary to the rules nahw. From here finally Zakaria concludes that the Koran is not the work of God, but a bouquet of Muhammad, because God could do no wrong. What does Zakaria is a fragment of a long journey Orientalist in reviewing the Eastern world, especially the Islamic religion who has written neatly in history. By writing the book IârÃ¢b al-QurâÃ¢n al-KarÃ®m wa BayÃ¢nuh, al-Darwish wanted to prove that what is alleged Zakaria just nonsense. This book is written with a light and easy to understand language readers, especially for the orientalists who lack the ability to understand the science nahw and Arabic literature